Zero-Day Reconciliation of BitTorrent Users With Their ISPs - Slot, Marco; Costa, Paolo; Pierre, Guillaume; Rai, Vivek (The 15th International European Conference on Parallel and Distributed Computing (Euro-Par'09), Delft, The Netherlands, August 2009., 2009)
BitTorrent users and consumer ISPs are often pictured as having opposite interests, with end-users aggressively trying to improve their download times, while ISPs throttle this traffic to reduce their costs. However, inefficiencies in both download time and quantity of long-distance traffic originate in BitTorrent randomly selecting peers to interact with. We show that biasing the link selection allows one to reduce both median download times by up to 32 and long-distance traffic by up to 16. This optimization can be deployed by modifying only the BitTorrent trackers. No external infrastructure nor specialized client-side software deployment is necessary, thereby facilitating the adoption of our technique.